2015
DOI: 10.4314/ahs.v15i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Activity limitations and participation restrictions experienced by people with stroke in Musanze district in Rwanda

Abstract: Background: Stroke is a major cause of long-term disability. Information regarding the limitations in activity and participation experienced by patients with stroke in a specific setting such as Musanze district in Rwanda would assist to develop the rehabilitation programmes that would take into consideration the functional challenges experienced post stroke. Objective: To explore the activity limitations and participation restrictions experienced by people with stroke in Musanze district in Rwanda. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Hand function is necessary for performing activities in almost all contexts. In the cultural context of this study, hand function might be even more vital than in high-income countries because more households in Uganda earn their living from work for which physical strength and fine motor ability are essential, such as for gardening, construction work and handicrafts; this is also shown in a study from Rwanda (Urimubenshi 2015). Any hand impairment could have been perceived as a serious restriction to participation in daily life.…”
Section: Discussionmentioning
confidence: 75%
“…Hand function is necessary for performing activities in almost all contexts. In the cultural context of this study, hand function might be even more vital than in high-income countries because more households in Uganda earn their living from work for which physical strength and fine motor ability are essential, such as for gardening, construction work and handicrafts; this is also shown in a study from Rwanda (Urimubenshi 2015). Any hand impairment could have been perceived as a serious restriction to participation in daily life.…”
Section: Discussionmentioning
confidence: 75%
“…Hand function has been proven to account for 32% of the single most important indicators of global recovery after stroke among people <65 years, one year after stroke(114).In Studies II and IV, the greatest perceived impact of stroke was shown in the domains of Strength, Participation and Hand function compared to previous studies(115,35). That might be due to the dependency of a good hand function as the main facilitator of participating and making everyday life and work in Uganda, as shown in a study from Rwanda(116). It seems as if most daily occupations in low-income countries require more motor function/strength for their accomplishment than in high-income countries.…”
mentioning
confidence: 84%
“…Currently more than 300 patients are estimated to suffer from podoconiosis in the study district [10]. Musanze has a population of 416,000 residents [12], of which 91% are farmers [13]. The presence of five volcanoes in this district makes the soil of this region rich in silica, which accumulate from the disintegration of larva in regions of high altitude [14].…”
Section: Settingmentioning
confidence: 99%